Phenomenological psychiatry and literature: guardians of the “lifeworld” - Jerotić, Stefan (Engrami, 2025)
This paper explores the deep parallels between phenomenological psychiatry and the modern novel, arguing that both disciplines act as “guardians” of the lived world (Lebenswelt) against the reductive tendencies of modern scientism. Drawing from phenomenological psychiatry – particularly the work of Jaspers, Minkowski, Binswanger, Fuchs, Sass, and Parnas – and literary modernism as articulated by Kundera and others, I show how both psychiatry and literature illuminate the subtle textures of subjective experience, including temporality, embodiment, and intersubjectivity. Literary modernism, exemplified in the works of Kafka, Woolf, Proust, and Kundera, not only anticipates but extends the phenomenological exploration of disturbances in these experiential structures, such as those seen in depression, schizophrenia, and trauma. By juxtaposing phenomenological psychiatry’s clinical accounts with literary portrayals, the paper reveals how the novel’s narrative imagination offers “eidetic” insights into lived experiences that exceed positivist, objectifying models of mind. The analysis extends to Serbian and Yugoslav literature, showing how authors such as Petrović, Kiš, Crnjanski, Pavić, Pekić, and Živković have crafted intricate narratives that align with phenomenological psychiatry’s emphasis on the relational and historical embedding of subjectivity. Ultimately, this comparative analysis argues that both literature and phenomenological psychiatry fulfill an indispensable role: to safeguard and deepen our understanding of the lived world in an era dominated by abstraction and reductionism.